Age Periods Of Human Life - Dyussenbayev, Akhmet (Advances in Social Sciences Research Journal, 2017)
In 2015, the World Health Organization under the United Nations officially revised the age standards. A person is now considered young before 44 years of age. According to the new age classification, the young age is from 25 to 44, middle age is 44-60, elderly age is 60-75, senile age is 75-90 and long-livers are after 90. This international standard is made without taking into account the objective regularities of the development physiology and psychology throughout the whole life in the course of rapid growth in youth, smooth development in mature age and the subsequent gradual aging of the human body.